ANALISIS PENGARUH KUALITAS PRODUK, HARGA DAN SALURAN DISTRIBUSI TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Konsumen Di T oko Bluder Cokro Jl. Hayam Wuruk Madiun) - Elly Yuniar Nitawati (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2019)
The research problem can be identified, namely whether Product Quality, Price and Distribution Channels simultaneously have a significant effect on Purchasing Decisions. Does the variable Product Quality, Price and Distribution Channels partially have a significant effect on Purchasing Decisions. Which variable between Product Quality, Price and Distribution Channels has dominant influence on Purchasing Decisions. Based on the background and formulation of the problem above, it can be explained that this study aims to analyze and prove the effect of the variable Product Quality, Price and Distribution Channels simultaneously has a significant influence on Purchasing Decisions. Analyzing and proving the influence of Product Quality, Price and Distribution Channels partially has a significant influence on Purchasing Decisions. Analyze which variables have the dominant influence on Purchasing Decisions. Based on the test results show the t-value of the product quality variable (X1), is greater than the value of t-table (5.627> 1.984) and the significance value (sig) is smaller than the required α (0.000 <0.05). These results indicate that the product quality variable has a positive and significant influence on purchasing decisions at Bluder Cokro Madiun. The t-value of the Price variable (X2) is greater than the value of t-table (3.015> 1.984) and the significance value (sig) is smaller than the required α (0.003 <0.05). These results indicate that the price variable has a positive and significant influence on purchasing decisions at Bluder Cokro Madiun. The t-value of the distribution channel variable (X3) is greater than the t-table value (2,360> 1,984) and the significance value (sig) is smaller than the required α (0.020 <0.05). These results indicate that the distribution channel variable has a positive and significant influence on purchasing decisions at Bluder Cokro Madiun. the results of the simultaneous test analysis of the three independent variables namely Product Quality (X1), Price (X2), and Distribution Channels (X3) significantly influence the Cokro Bluder Purchasing Decision. as evidenced by the calculated F-value 111,689> F table 2.72, with a significance level of less than 0.05. The existence of the three independent variables is strengthened by the contribution of the independent variable with the dependent variable that has an adjusted R square value of 0, 770 or 77.0%. This 23% figure states that the three independent variables are able to show a significant contribution in determining the dependent variable (purchasing decision). Keywords: